2001
DOI: 10.1016/s0092-8674(01)00271-9
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Analyses of DNA Recognition by the AML1/Runx-1 Runt Domain and Its Allosteric Control by CBFβ

Abstract: The core binding factor (CBF) heterodimeric transcription factors comprised of AML/CBFA/PEBP2alpha/Runx and CBFbeta/PEBP2beta subunits are essential for differentiation of hematopoietic and bone cells, and their mutation is intimately related to the development of acute leukemias and cleidocranial dysplasia. Here, we present the crystal structures of the AML1/Runx-1/CBFalpha(Runt domain)-CBFbeta(core domain)-C/EBPbeta(bZip)-DNA, AML1/Runx-1/CBFalpha(Runt domain)-C/EBPbeta(bZip)-DNA, and AML1/Runx-1/CBFalpha(Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
199
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(206 citation statements)
references
References 54 publications
6
199
1
Order By: Relevance
“…The RUBY assay indicates a direct interaction between BRO-1 and RNT-1 and EMSA studies demonstrate that BRO-1 is required for robust binding of RNT-1 to the Runx consensus DNA binding site, consistent with other studies of CBF␤ function (Bushweller, 2000;Li et al, 2003;Nagata and Werner, 2001;Tahirov et al, 2001;Yan et al, 2004). Furthermore, our experiments show that BRO-1 3913 RESEARCH ARTICLE CBF␤ factor in C. elegans development dramatically increases the specificity of RNT-1-DNA binding, thereby extending previous studies of CBF␤/Runx interactions.…”
Section: Co-overexpression Of Bro-1 and Rnt-1 Causes Seam Cell 'Tumours'supporting
confidence: 87%
See 3 more Smart Citations
“…The RUBY assay indicates a direct interaction between BRO-1 and RNT-1 and EMSA studies demonstrate that BRO-1 is required for robust binding of RNT-1 to the Runx consensus DNA binding site, consistent with other studies of CBF␤ function (Bushweller, 2000;Li et al, 2003;Nagata and Werner, 2001;Tahirov et al, 2001;Yan et al, 2004). Furthermore, our experiments show that BRO-1 3913 RESEARCH ARTICLE CBF␤ factor in C. elegans development dramatically increases the specificity of RNT-1-DNA binding, thereby extending previous studies of CBF␤/Runx interactions.…”
Section: Co-overexpression Of Bro-1 and Rnt-1 Causes Seam Cell 'Tumours'supporting
confidence: 87%
“…1) (reviewed by Kagoshima et al, 2007). In addition to the low overall homology, it also lacks the conserved region in fly and mammalian CBF␤ corresponding to the sequences between the beta sheets, ␤3 and ␤6, which might be expected to interfere with the positioning of the Runx interaction domain around ␤3 and ␤5 (Tahirov et al, 2001) (Fig. 1B).…”
Section: Bro-1 Mutants Have Missing Rays As a Results Of Failures In Vmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenotype of PEBP2b -/-mice is almost identical to that of Runx1 -/-mice [9][10][11], which suggests that PEBP2b is required for Runx1 function in vivo. While PEBP2b does not bind to DNA, it increases the DNAbinding affinity of Runx1 in an allosteric manner, thus elevating the transcriptional activity of the PEBP2/CBF complex [12,13]. However, it has also been shown that the Runx1/PEBP2b heterodimer does not form readily.…”
Section: Introductionmentioning
confidence: 99%